A study on the cavitating flow around an elliptical disk-shaped cavitator for non-body-of-revolution underwater vehicles. Issue 1 (31st December 2023) - Chen, Guangyao; Sun, Tongshuai; Yang, Shaoqiong; Miao, Zhanzhan; Tan, Hua
Abstract : Supercavitation has been recently presented as an effective method for the drag reduction of underwater vehicles. However, maintaining the supercavitating state requires a lot of energy, making vehicles difficult to control. Therefore, it is necessary to design an underwater vehicle with low drag in the fully wetted state while being able to move at ultra-high speed in the supercavitating state. In this study, a detachable fairing design for underwater vehicles is proposed, which has the advantage of increasing the total voyage and avoiding the problem of difficult steering in the supercavitating state. On the other hand, the study of non-body-of-revolution (non-BOR) has become a prevalent area of interest in the shape design of underwater vehicles. The cavity generated by an elliptical disk-shaped cavitator is studied numerically. It is found that the cavity profile on the cross-section near the cavitator is approximately elliptical. The cavity length of an elliptical disk-shaped cavitator is almost the same as that of a disk-shaped cavitator when they have the same inflow area. Based on these two characteristics, the parameters of the internal elliptical disk-shaped cavitator are optimized, which provides a promising strategy for the issue of cavitators increasing drag in a fully wetted state.